Beyond the Classroom Walls: Metacognitive awareness in traditional and online setting - Radka Miháliková (Pedagogika)
Objective – The aim of this study is to assess and compare the metacognitive awareness of university students in online and in-person learning environments. Secondly, the study aims to explore the students’ preferences for online and in-person learning to compare themetacognitive awareness of students based on their preferences.